Vascular variant of Eagle syndrome: a review - Tadjer, Joy; Béjot, Yannick (Frontiers in Neurology, 2024)
Eagle syndrome is defined as an elongated styloid process (ESP) that compresses nearby vasculo-nervous structures. The vascular variant of Eagle syndrome can lead to neurological symptoms including syncope, transient ischemic attack, or stroke; however, it has also been associated with other atypical presentations, making its diagnosis challenging. This review aimed to depict the characteristics of patients with the symptomatic vascular variant of Eagle syndrome. The literature search identified 56 reported cases of vascular variants of Eagle syndrome, with a mean age at onset of 51 years (range: 15–85 years), and the male-to-female ratio was 2:4. The ESP was bilateral in 63% of the cases, and the mean length was 48 mm (range: 31–77 mm). Vascular complications were mostly represented by internal jugular vein (IVJ) stenosis (n = 28), followed by internal carotid artery (ICA) dissection (n = 15). Additionally, eight cases of ICA thrombosis and two cases of severe chronic stenosis of the ICA > 90% were reported. Vascular complications may lead to cerebral ischemia due to either a thromboembolic mechanism or, less frequently, reduced blood flow. Laminar cortical necrosis, as a cerebral complication of ICA compression, was exceptionally described in one case, and such an atypical clinical presentation may be regarded as a diagnostic pitfall.